Analisis Optimalisasi Manajemen Operasional (Pada Teen Canteen Berbasis Media Digital dan Kinerja Sumber Daya Manusia) - Sida Larasati; Diana Apristya Nugraheni; Retno Widari (International Forum of Researchers and Lecturers, 2026)
The growth of the culinary industry requires small-scale food businesses to implement effective and efficient operational management. This study analyzes the optimization of operational management at Teen Canteen by examining the use of digital systems, staff performance, the implementation of Standard Operating Procedures (SOP), and operational constraints. A descriptive qualitative approach was employed, with data collected through semi-structured interviews and direct observation. The informant was purposively selected, namely the Head Bar, who is directly involved in daily operational activities. Data analysis was conducted using the Miles and Huberman model. The findings indicate that Teen Canteen’s operational management has not been optimally implemented due to the discontinuation of digital cashier systems, reliance on manual transaction and inventory records, and inconsistent SOP implementation. Although staff performance is generally adequate, issues related to discipline and service responsiveness remain. This study recommends reintroducing digital cashier systems and establishing written SOPs to improve operational effectiveness.